Restructuring of Epibacterial Communities on Fucus vesiculosus forma mytili in Response to Elevated pCO2 and Increased Temperature Levels - Mensch, Birte; Neulinger, Sven C.; Graiff, Angelika; Pansch, Andreas; Künzel, Sven; Fischer, Martin A.; Schmitz, Ruth A. (Frontiers in Microbiology, 2016)
Marine multicellular organisms in composition with their associated microbiota – representing metaorganisms – are confronted with constantly changing environmental conditions. In 2110, the seawater temperature is predicted to be increased by approximately 5 °C, and the atmospheric carbon dioxide partial pressure (pCO2) is expected to reach approximately 1,000 ppm. In order to assess the response of marine metaorganisms to global changes, e.g. by effects on host-microbe interactions, we evaluated the response of epibacterial communities associated with Fucus vesiculosus forma mytili (F. mytili) to future climate conditions. During an 11-week lasting mesocosm experiment on the island of Sylt (Germany) in spring 2014, North Sea F. mytili individuals were exposed to elevated pCO2 (1,000 ppm) and increased temperature levels (∆+5 °C). Both abiotic factors were tested for single and combined effects on the epibacterial community composition over time, with three replicates per treatment. The respective community structures of bacterial consortia associated to the surface of F. mytili were analyzed by Illumina MiSeq 16S rDNA amplicon sequencing after 0, 4, 8 and 11 weeks of treatment (in total 96 samples). The results demonstrated that the epibacterial community structure was strongly affected by temperature, but only weakly by elevated pCO2. No interaction effect of both factors was observed in the combined treatment. We identified several indicator operational taxonomic units (iOTUs) that were strongly influenced by the respective experimental factors. An OTU association network analysis revealed that relationships between OTUs were mainly governed by habitat. Overall, this study contributes to a better understanding of how epibacterial communities associated with F. mytili may adapt to future changes in seawater acidity and temperature, ultimately with potential consequences for host-microbe interactions.